The Spectrum of Quantum Dots Film for UV CCD - Lin Jiang; Haojie Sun; Bang-lian Xu; Da-wei Zhang; Chun-xian Tao; Yuan-shen Huang; Zheng-ji Ni; Song-lin Zhuang (Journal of Spectroscopy)
A new kind of UV-responsive film with quantum dots (QDs) fabricated by a spin-coating method is proposed in this paper. In a previous study, the monolayer QDs film is deposited onto fused silica slides by the spin-coating way, which has some luminous problem. The introduction of composite QDs coating which adds PEDOT:PSS and poly-TPD films to the monolayer QDs film is found to have excellent performance. The reason can be that PEDOT:PSS and poly-TPD weaken the scattering and enhance the emitting of quantum dot fluorescence. The intensity of photoluminescence (PL) for composite QDs coating is dozens of times stronger than that for monolayer QDs film. Experiment results show that this composite coating has excellent fluorescent properties and emits a blue purple glow together a wide excitation spectrum field from 190 nm to 300 nm. The spectrum of the composite coating matches accurately with the detected zone of CCD, which achieves an outstanding UV-responsive coating for conventional silicon-based image sensors.